Relationship between resilience level and anxiety level of family who has elderly in facing the covid-19 pandemic - Hidayatus Sya’diyah; Diyan Mutyah; Ayu Citra Mayasari; Sukma Ayu Candra Kirana; Mustika Myra (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
The Covid-19 pandemic has a psychological effect on people with anxiety. In terms of individual psychological suffering, a major factor that is important is psychological resilience. The purpose of this study is to determine the relationship between the level of anxiety and the level of resilience of families who have the elderly during the Covid-19 pandemic at the Ketajen Village, Gedangan District. The design of this study used a cross-sectional design with a sample of 171 respondents. The sampling technique was selected by using simple random sampling. Reference levels are measured using a Connor-Davidson Resilience Scale (CD-RISC) and anxiety levels are measured using a Hamilton Rating Scale for Anxiety (HRS-A) with a spearman rho analysis test (p< 0.05). The results showed that most families had moderate levels of resilience as many as 121 respondents (70.8%) and most families experienced mild anxiety levels as many as 121 respondents (70.8%). Spearman Rho test shows that the value of r = -0.313 with a value of Ï = 0.000 (Ï%). The results show that there is a relationship between the level of resilience and the level of anxiety of families who have the elderly during the Covid-19 pandemic at the Ketajen Village, Gedangan District. The implications of this study suggest that high levels of resilience allow for lower levels of anxiety. So, with the ability of a person's resilience will be able to take the meaning of failure and try better than he ever did, thereby reducing the risk of anxiety.